The Function of Female Silence in The Kitchen God’s Wife by Amy Tan - Rawaa Jawad Kadhim; Idrees Samir Deli; Nadia Ali Akbar (Sociometry Journal of Social Science, Art and Humanity, 2022)
This study contributes to the understanding of silence, which contradicts the traditional thought of believing that silence reflects the inability to interact with others or express oneself. Amy Tan’s novel The Kitchen God’s Wife has been taken as an example to argue the idea above, considering Margaret E. Montoya’s views that silence can be a means of resistance against oppression or a product of oppression. Female characters in the novel can speak words and phrases, but they remain silent for reasons that will explain in the research.